(untitled) (Intent Research Scientific Journal, 2023)
The article describes lexical and semantic features of the representation of the ethno-cultural component of semantics by units of an indirectly derived nomination with the head component based on the material of the thematic area of Russian phraseology "Mind - Stupidity"